Factors that influence employee retention at Sime Darby Plantations Sdn Bhd / Masitah Safian (Faculty of Business Management, 2007)
Employee retention is one of evaluation aspect in work behavior and performance, which has been emphasized by all the organization to ensure the successful of organization's goal. In this research, the study is made towards employee retention among staff of Sime Darby Plantations Sdn Bhd located at Subang. The research objectives are to to determine the responds from the factors towards influence employee retention in Sime Darby Plantation Division,to identify the difference in the perceptions of retentions factors among employee at Sime Darby Plantations Divisions, to identify relationship between supervision, interpersonal relationship, work itself, working condition, reward benefit and the employee retention and lastly to Provide recommendations on how to retain employee in sime Darby. For the purpose of the study, exploratory research was deployed in order to identify factors that contributed to employee retention. Simple random sampling has been utilized with 73 respondents or the sample size. Self- administrated questionnaire was used as the survey instrument besides internal interview as the source of primary data. By using the analysis generated by SPSS (Statistical Package for the Social Science), resulted are analyzed and deduction being drawn and prove by looking at the data analysis and cross tabulation with Chi-square testing. Finally, the finding from this study concludes that most of the staff of Sime Datby Plantations Sdn Bhd have moderate with the factors, and certain factors should be reviewed by Sime Darby Plantations Sdn Bhd.